EKSPLORASI GAYA ARSITEKTUR MODERN: Studi Kasus Masjid Islamic Center Tulang Bawang Barat - Bernard Andrew; Victor Daniel Simanjuntak; Sultan Rasyad Henkhazara; Dewi Fadilasari (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: Abstract: Architecture as a marker of civilization brings its characteristics in each era. The West Tulang Bawang (Tubaba) Islamic Center Mosque is a mosque with a center for Islamic activities in it. Designed with unique architecture and is different from other general mosque. In the application of architecture, the Tubaba Islamic Center Mosque has a theoretical value in terms of function, form, and meaning that cannot be separated from the Islamic religious elements in it. The function is applied as a center for Islamic activities, a different form from mosques in general but with Islamic ornaments that do not eliminate the mosque's signature, and also the meaning that is applied from construction, and elements to the concept of the building. The modern architectural style at the Tubaba Islamic Center Mosque follows the characteristics of the modern architectural version of the International Style.Keyword::Architecture, Mosque, ModernAbstrak: Arsitektur sebagai penanda peradaban membawa suatu ciri khas sendiri dalam setiap zamannya. Masjid Islamic Center Tulang Bawang Barat (Tubaba) adalah sebuah masjid dengan pusat kegiatan kegiatan islami didalamnya. Dirancang dengan arsitektur unik dan berbeda dengan masjid pada umumnya. Untuk penerapan di bidang arsitektur, Masjid Islamic Center Tubaba memiliki nilai teori secara fungsi, bentuk dan makna yang tidak terlepas dari unsur keagamaan Islam didalamnya. Fungsi diterapkan sebagai pusat kegiatan islami, bentuk yang berbeda dari masjid pada umumnya namun dengan ornamen Islam yang tidak menghilangkan signature masjid, dan juga makna yang diterapkan dari kontruksi, elemen sampai dengan konsep bangunan. Gaya arsitektur modern pada Masjid Islamic Center Tubaba mengikuti ciri dari arsitektur modern versi International Style.Kata Kunci: Arsitektur, Masjid, Modern